Vision-Threatening Behcet’s Disease: Severity of Ocular Involvement Predictors - Mohammed A. Hussein; Iman M. Eissa; Ahmed A. Dahab (Journal of Ophthalmology)
Purpose. To examine and spot systemic findings commonly associated with a serious form of ocular Behcet’s disease. This could potentially help ophthalmologists categorize their patients based on future risk and plan treatment accordingly. Subjects and Methods. The data of 249 patients with Behcet’s disease were examined thoroughly. Correlations between systemic and ocular findings were recorded. Patients were further subgrouped by the authors as having a vision-threatening form of the disease or not. Regression analysis was done to spot predictors for a vision-threatening form of the disease. Results. The presence of systemic vasculitis and oral and genital ulcers in a patient with Behcet’s disease was found to be associated with a milder form of ocular affection or none at all and vice versa. Certain correlations between findings were also found. Conclusion. Certain findings in Behcet’s disease may act as predictors for the severity of ocular affection. Directing our attention to these factors by the internist and ophthalmologist can help plan the frequency of follow-up as well as the aggressiveness of treatment in patients with Behcet’s disease.